Analisis Fundamental Saham Sektor Consumer Goods LQ45 Pada Masa Pandemi Covid-19 - Vidada, Irwin Ananta; Saridawati, Saridawati (JURNAL ADMINISTRASI KANTOR; Vol 10 No 1 (2022): Jurnal Administrasi Kantor (Juni 2022), 2022)
It is known that world conditions, including Indonesia, are currently still hit by the Covid-19 pandemic, which has an impact on the stock market and economic growth. The Composite Stock Price Index (JCI) has decreased, as has economic growth.Reviews and measurements of the toughness of the fundamental performance of certain company stocks in the Consumer Sector that are included in the LQ45 index in going through the Covid-19 pandemic are interesting to observe.The LQ45 index is an index of choice based on the performance of 45 stocks that have high liquidity, large market capitalization and good company fundamentals. LQ45 shares themselves are often the choice for investors to invest. To predict stock movements, investors generally use technical analysis and fundamental analysis.While technical analysis predicts future stock prices using historical prices, fundamental analysis uses information from inside and outside the company, such as performance, business competitors, industry and even macro-microeconomics, as well as market information. Fundamental analysis is usually used by long-term investors who make the long-term sustainability of the company an important consideration. In general, there are a number of indicators in Fundamental Analysis including ROE (Return Of Equity), PBV (Price Book Value), PER (Price Earning Ratio), EPS (Earning Per Share), Dividend Yield, and DER (Debt Earning Ratio).Based on the results of research on fundamental analysis using financial statements and stock prices in the third quarter of 2021 (annualized) the Consumer Goods sector listed on the Indonesia Stock Exchange indexed LQ45 from the sample studied from 1 to 4 ranks as follows: 1. INDF, 2. JPFA, 3. ICBP and 4. UNVR.   Keywords: Stock Investment, Fundamental Analysis, Financial Performance.